Perceptions, facilitators and barriers to the implementation of interpersonal group therapy to treat depression among people living with HIV in Senegal: a qualitative study - Bernard, Charlotte; Mané, Idrissa; Ziadeh, Salaheddine; Tine, Judicaël Malick; Diaw, Abibatou; Benzekri, Noëlle; Ndiaye, Ibrahima; Samba, Oumar; Font, Hélène; Bottai, Thierry; Jacquesy, Laurent; Verdeli, Helen; et al. (Frontiers in Public Health, 2024)
Background: Depression is highly prevalent in people living with HIV (PLWH) but remains under treated in Sub-Saharan Africa. In this context, we conducted the first study of Group Interpersonal Therapy (IPT) to treat depression in PLWH in Senegal. We assessed the perceptions and experiences of patients and group facilitators, as well as barriers to implementation.Methods: This study was conducted at the Fann National University Hospital Center in Dakar, the urban capital of Senegal. Qualitative data were collected during the implementation phase (February to June 2020 and then from January to February 2021), with a 6-month pause due to the COVID-19 pandemic. Twenty-five patients and three group facilitators were individually interviewed by a socio-anthropologist. Qualitative data were analyzed thematically.Results: Group IPT was perceived as successful and beneficial by patients and facilitators. Patients reported positive experiences with group IPT and sustained outcomes. Beyond improving depressive symptoms, patients reported improvements in their social and professional lives, and the development of skills to prevent relapse. Group facilitators noted the benefits of therapy for their patients and for their professional skills, reporting greater clinical competence and improved supportive skills. Challenges to intervention implementation included confidentiality and patient privacy concerns, healthcare accessibility issues, and time demands.In this first qualitative study of group IPT for depression in PLWH in Senegal, participants described both positive experiences with the intervention and challenges to its implementation. Future studies, conducted in suburban and rural communities outside of Dakar, would further inform the implementation of IPT in Senegal.